Coral Recruitment on Artificial Patch Reefs Deployed in The Marginal Reefs: Effect of Multilevel Substrate on Density of Coral Recruit - Munasik Munasik; Agus Sabdono; Eunike Dorothea Hutapea; Sugiyanto Sugiyanto; Denny Nugroho Sugianto (Jurnal Segara, 2021)
A study of coral recruitment on Artificial Patch Reefs (APR) was performed in the marginal reef of Panjang Island, Central Java (Java Sea) to examine whether multilevel substrates of APR affect the density of coral recruits. Long-term and short-term observations were applied in yearly monitoring 2017-2019 and biweekly observations for 3 months in early 2019. Coral recruitment significantly varied among level substrates of APR (F(a,b) .05=3.08; p-value<0.05) and there was a significant difference at the beginning of the year (F(a,b) .05=5.52; p-value<0.05). The density of recruits on the substrates after 4 years post-deployment of APRs was 0.2 to 129.2 m-2 while the recruitment rate within short-term observations was 0.28-1.28 m-2 per month. The highest coral recruitment occurred at the middle to the top level of APR, while the lowest recruitment was found in the lowest level of APR. This is possibly due to high resuspension from the seabed. Oulastrea was dominant in both long- and short-term recruitment periods while Pocillopora was rare due to post-settlement mortality which trigger the overgrown coral-killing sponges. The results indicated that the adaptation of coral recruitment in the marginal environment is determined by the high recruitment of the small-colony coral species which possessed stress-tolerant for turbidity disturbance, such as Oulastrea crispata. This study suggested that the multilevel substrates, Artificial Patch Reefs (APR) are one of the reef rehabilitation methods which can be applied in the marginal environment enhancing coral recruitment.